The Relation Between Smartphone Use with Forward Head Posture Occurrence in Undergraduate Physiotherapy Student - Daniel, Grady; Anak Agung Gede Angga Puspa Negara; Indira Vidiari Juhanna; Ni Wayan Tianing (Universitas Udayana dan Diaspora Taipei Medical University, 2022)
Introduction: College students use smartphones with a high level of use, high levels of smartphone use due to various purposes such as academic and non-academic needs, and prolonged use of smartphones with poor posture can cause permanent changes in posture to their users. One of the posture changes that can occur is the forward head posture (FHP). Methods: The research design was a cross-sectional study conducted from August to December 2021 with a population of Udayana University Physiotherapy students who met the inclusion and exclusion criteria. The sampling technique in this study was purposive sampling, and obtained 62 samples. This study used the YourHour application and Web Plot Digitizer to measure the duration of smartphone use and the craniovertebral angle, respectively. Data were analyzed by SPSS 16.0 to determine the relationship between smartphone use with forward head posture occurrence in physiotherapy students. Results: The majority of students who were in the research sample used smartphones with a high level of duration, as many as 46 samples; in 46 samples with a high level of duration found, 28 samples experienced forward head posture, in students with moderate and low duration levels, forward head posture is rare. The results of the chi-square obtained are p-value = 0.009. it indicates that there is a relationship between the dependent variable and the independent variable. Conclusion: There is a relationship between the duration of smartphone conditions and forward head posture in students of the Physiotherapy Undergraduate Study Program, Faculty of Medicine, Udayana University. In this study, it can be seen that the forward head posture is the majority of smartphones with high intensity.